A Proposal for Clinical Genetics (Genetics in Medicine) Education for Medical Technologists and Other Health Professionals in Japan - Kohzaki, Hidetsugu (Frontiers in Public Health, 2014)
Since the completion of the Human Genome Project, technology has developed markedly in fields such as medical genetics and genetic counseling in the medical arena. In particular, this technology has advanced the discovery of and ways of understanding various genes responsible for genetic diseases, and genetic polymorphisms thought to be associated with disease. Some have been implicated as factors in common lifestyle diseases and have increased the significance of genetic testing. In Japan, doctors and other health professionals, such as nurse and medical technologists have been engaged in genetic testing and genetic disease treatment. Chromosomal and gene aberrations were detected mainly by medical technologists. However, due to the nature of medical technologists who have to provide various clinical tests, such as blood test, pre-medical technology students are required to cover tremendous knowledge of different academic fields to pass the national exam. Therefore, the time allowed for such students to study chromosomal and gene analysis is quite limited. Moreover, they are forced to enter the medical setting without receiving sufficient training. Among them, only few medical technologists specialize in chromosomal and gene analysis. However, with the advancement of clinical genetics and development of chromosomal and gene analysis, conducting clinical practice is becoming more and more difficult for medical technologists who just passed the national exam. Also, doctors and other health professionals have not been able to keep up with service demands either. This paper attempts to address knowledge and skills gaps (especially clinical genetics, English, and ICT literacy) of medical technologists and we propose educational methods to prepare medical genetics professionals in Japan to meet these gaps.